2007
DOI: 10.1002/qua.21433
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of ignition reactions of linear symmetrical monoethers as potential diesel fuel additives: DFT calculations

Abstract: This work investigates the chemical reactivity of four linear symmetrical monoethers with molecular oxygen. Such oxygenated compounds may be considered as potential diesel fuel additives in order to reduce the ignition delay in diesel fuel engines. For this purpose, a kinetic study is proposed to clarify the relation between the molecular structure of the fuel molecule and its ignition properties. To this end, DFT calculations were performed for these reactions using B3LYP/6-311G(d,p) and BH&HLYP/6-311G(d,p) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Francisco performed theoretical calculations on reaction and confirmed that the bimolecular reaction had a lower barrier height (217 and 195 kJ mol –1 at the PMP4/6-311G­(2df,2p)//UMP2/6-311G­(2df,2p) and CCSD­(T)/6-311G­(2df,2p)//UMP2/6-311G­(2df,2p), respectively) compared with the C–O bond fission (339–345 kJ mol –1 ), , and could be the primary initiation reaction during the oxidation of DME. Marrouni and co-workers in a theoretical study also verified that introducing an ether bridge in a hydrocarbon molecule increased the reactivity of the hydrogen atoms toward O 2 to shorten the autoignition delay time and reported barriers for reactions to be 154.64 and 178.28 kJ mol –1 , respectively, at the B3LYP/6-311G­(d,p) and BH&HLYP/6-311G­(d,p) levels.…”
Section: Introductionmentioning
confidence: 83%
“…Francisco performed theoretical calculations on reaction and confirmed that the bimolecular reaction had a lower barrier height (217 and 195 kJ mol –1 at the PMP4/6-311G­(2df,2p)//UMP2/6-311G­(2df,2p) and CCSD­(T)/6-311G­(2df,2p)//UMP2/6-311G­(2df,2p), respectively) compared with the C–O bond fission (339–345 kJ mol –1 ), , and could be the primary initiation reaction during the oxidation of DME. Marrouni and co-workers in a theoretical study also verified that introducing an ether bridge in a hydrocarbon molecule increased the reactivity of the hydrogen atoms toward O 2 to shorten the autoignition delay time and reported barriers for reactions to be 154.64 and 178.28 kJ mol –1 , respectively, at the B3LYP/6-311G­(d,p) and BH&HLYP/6-311G­(d,p) levels.…”
Section: Introductionmentioning
confidence: 83%
“…). The capacity of some ether oxygenated additives to improve cetane number can be explained by the presence of an oxygen bridge that increase the reactivity of the hydrogen atoms in the hydrocarbon chain of the neighboring carbons contributing to the onset of combustion [Abu-Rachid et al, 2003;Marrouni et al, 2008]. For example, the comparison between CN values of dimethyl ether (DME) (55-60) and propane (−20) suggests that the 6 hydrogen atoms of the methyl groups of CH 3 -O-CH 3 are much more reactive toward oxygen than the ones in CH 3 -CH 2 -CH 3 .…”
Section: Additives For Fuelsmentioning
confidence: 99%